Disease severity in K/BxN serum transfer-induced arthritis is not affected by IL-33 deficiency - Martin, Praxedis (BioMed Central, 2013)
INTRODUCTION: Interleukin (IL)-33 is a cytokine of the IL-1 family, which signals through the ST2 receptor. Previous work suggested implication of the IL-33/ST2 axis in the pathogenesis of human and mouse arthritis. Here, we directly investigated the role of endogenous IL-33 in K/BxN serum transfer-induced arthritis by using IL-33 knockout (KO) mice. METHODS: Arthritis was induced by injection of complete K/BxN serum or purified IgG. Disease severity was monitored by clinical and histological scoring. RESULTS: K/BxN serum transfer induced pronounced arthritis with similar incidence and severity in IL-33 KO and wild-type (WT) mice. In contrast, disease development was significantly reduced in ST2 KO mice. IL-33 expression in synovial tissue was comparable in arthritic WT and ST2 KO mice, and absent in IL-33 KO mice. Transfer of purified arthritogenic IgG instead of complete K/BxN serum also resulted in similar arthritis severity in IL-33 KO and WT mice, excluding a contribution of IL-33 contained in the serum of donor mice to explain this result. We investigated additional potential confounding factors, including purity of genetic background, but the mechanisms underlying reduced arthritis in ST2 KO mice remained unclear. CONCLUSIONS: The data obtained with IL-33 KO mice indicate that endogenous IL-33 is not required for the development of joint inflammation in K/BxN serum transfer-induced arthritis. On the contrary, arthritis severity was reduced in ST2 KO mice. This observation might relate to IL-33 independent effects of ST2, and/or reveal the existence of confounding variables affecting the severity of joint inflammation in these KO strains.